Optimal resource allocation in stochastic activity networks via the electromagnetism approach: a platform implementation in Java - Tereso, Anabela Pereira (2009)
An optimal resource allocation approach to stochastic multimodal projects had been previously developed by applying a Dynamic Programming model which proved to be very demanding computationally. A new approach, the Electromagnetism-like Mechanism, has also been adopted and implemented in Mat lab, to solve this problem. This paper presents the implementation of the Electromagnetism approach using an Object Oriented language, Java, and a distributed version to be run in a computer network, in order to take advantage of available computational resources.